1988
DOI: 10.1017/s0950268800029344
|View full text |Cite
|
Sign up to set email alerts
|

Detection of specific IgM in varicella and herpes zoster by antibody-capture redioimmunoassay

Abstract: A simple and sensitive M antibody-capture radioimmunoassay (MACRIA) is described which utilizes crude commercial VZV antigen and a single monoclonal anti-VZV antibody. This was compared to the immunofluorescence (IF) test for IgM antibody and was used to study IgM responses in sera from 261 patients with varicella and 220 patients with herpes zoster. With MACRIA, IgM antibodies were detected in all patients with varicella. The IgM antibodies appeared shortly after onset of rash, reached peak levels between 1 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0
1

Year Published

1988
1988
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 10 publications
1
21
0
1
Order By: Relevance
“…In the present study VZV-IgM was detected in all 18 patients with varicella, in 7 of these (38-9 %) in the acute-phase serum obtained within a few days after onset of symptoms. This is in agreement with the results of others [2,4,8]. Furthermore, VZV-IgM was detected in serum from 13 out of 19 (68-4 %) patients with herpes zoster.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…In the present study VZV-IgM was detected in all 18 patients with varicella, in 7 of these (38-9 %) in the acute-phase serum obtained within a few days after onset of symptoms. This is in agreement with the results of others [2,4,8]. Furthermore, VZV-IgM was detected in serum from 13 out of 19 (68-4 %) patients with herpes zoster.…”
Section: Discussionsupporting
confidence: 93%
“…Similar results have been obtained by others using both indirect assays as well as antibody-capture assays. In these reports VZV-IgM in patients with herpes zoster was detected by indirect radioimmunoassay in 69 % [4], by indirect immunofluorescense in between 50% and 78 % [1,2,8] and by AC-ELISA in between 50 % and 84% [6,7] of patients. In all studies the VZV-IgM response in patients with herpes zoster was found to be of a lesser magnitude compared to the response in patients with varicella and to be relatively shortlived.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations